2016
DOI: 10.7189/jogh.06.020901
|View full text |Cite
|
Sign up to set email alerts
|

Preventing delayed diagnosis of cancer: clinicians’ views on main problems and solutions

Abstract: BackgroundDelayed diagnosis is a major contributing factor to the UK’s lower cancer survival compared to many European countries. In the UK, there is a significant national variation in early cancer diagnosis. Healthcare providers can offer an insight into local priorities for timely cancer diagnosis. In this study, we aimed to identify the main problems and solutions relating to delay cancer diagnosis according to cancer care clinicians.MethodsWe developed and implemented a new priority–setting approach calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
2
17
0
Order By: Relevance
“…GPs’ views on the importance of closer links between primary and secondary care were identified in that and other studies 29 30. Our PCPs’ call for improved patient education and better access to diagnostic testing specialist care were also prioritised by GPs in a UK study 40. Our findings map across to the findings from qualitative research on patient-perceived barriers to early presentation and diagnosis of cancer, which have identified the need for better access to services for patients41 42 and better patient awareness of cancer symptoms42 as key issues.…”
Section: Discussionmentioning
confidence: 70%
“…GPs’ views on the importance of closer links between primary and secondary care were identified in that and other studies 29 30. Our PCPs’ call for improved patient education and better access to diagnostic testing specialist care were also prioritised by GPs in a UK study 40. Our findings map across to the findings from qualitative research on patient-perceived barriers to early presentation and diagnosis of cancer, which have identified the need for better access to services for patients41 42 and better patient awareness of cancer symptoms42 as key issues.…”
Section: Discussionmentioning
confidence: 70%
“…Symptom awareness and appraisal by patients and doctors is an important determinant of timely presentation and investigation [31][32][33][34] but the optimal design of early diagnosis interventions aimed at earlier recognition of possible cancer symptoms by members of the public and health-care professionals remains unclear. Alongside considerations such as cancer site incidence, psychosocial barriers to presentation, and the predictive value of symptoms, evidence about the associations between presenting symptoms and stage at diagnosis can help to guide the design of early diagnosis interventions.…”
Section: Discussionmentioning
confidence: 99%
“…During the first World Hepatitis Summit in 2015, Glasgow Declaration on Hepatitis committed all governments to eliminate viral hepatitis [17]. Successful policies and programs in prevention and treatment require the public’s awareness, attention, and action [31]. This study revealed several disconnections in the recognition and behavior steps necessary for hepatitis eradication and liver disease prevention, some of which are critical yet often overlooked in extant literature and policy discussion.…”
Section: Discussionmentioning
confidence: 99%